ANALISIS HUBUNGAN KUALITAS PELAYANAN, FITUR, DAN SOCIAL INFLUENCE TERHADAP REPUTASI PERUSAHAAN MELALUI KEPERCAYAAN MASYARAKAT - Hari Prabowo; Ani Yunaningsih (Scientia Regendi, 2020)
This study is conducted to analyze the effect of social influence on company reputation. The data used in this study are primary data and the data were collected through questionnaires which distributed to research samples of 400 electronic money users throughout Indonesia. Furthermore, the data analysis technique used for hypothesis testing is SEM PLS. The result of the research reveal that the social influence and e-money company reputation is considered good. Furthermore the research proved that social influence affect the reputation of Non-Bank and Non-Telecommunication Electronic Money Issuer Companies. From these results Non-Bank and Non-Telecommunication Electronic Money Issuer Companies are advised to increase the good social influence in order to improve the company reputation.